Mathematics Curriculum Of Grades 11th And 12th From The Perspective Of Stakeholders In The Sultanate Of Oman - Al-Hadidi, Mohammed Rashid Said (2010)

(untitled)
The purpose of this study was to explore the stakeholders' views toward mathematics curriculum of grades 11 and 12 in the Sultanate of Oman. The study examined supervisors, teachers, undergraduate students of higher education level and of private sector toward the content relevant of mathematics curriculum in grades 11 and 12, and supervisors and teachers' views toward quality of instructional strategies and assessment practices suggested in teacher guide and textbooks of applied mathematics in secondary school in Oman.